Asymptotic stability in delay nonlinear fractional differential equations - Ardjouni,A (Universidad Católica del Norte, Departamento de Matemáticas, 2016)
In this paper, we give sufficient conditions to guarantee the asymptotic stability of the zero solution to a kind of delay nonlinear fractional differential equations of order . By using the Banach’s contraction mapping principle in a weighted Banach space, we establish new results on the asymptotic stability of the zero solution provided that g (t, 0) = f (t, 0, 0) = 0, which include and improve some related results in the literature.